2004
DOI: 10.1161/01.cir.0000118497.44961.1e
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Dental Score and Prevalent Coronary Heart Disease

Abstract: Background-Oral infections have been postulated to produce cytokines that may contribute to the pathogenesis of coronary heart disease (CHD). We hypothesized that by estimating the combined production of inflammatory mediators attributable to several oral pathologies, we might be able to explain CHD with better precision. Methods and Results-A total of 256 consecutive Finnish cardiac patients from Kuopio University Hospital with angiographically confirmed CHD and 250 age-, gender-, and residence-matched noncar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 29 publications
5
69
0
4
Order By: Relevance
“…We have further improved the TDI formulated by Mattila and co-workers in our case-control study by developing a mathematical scoring system called the Asymptotic Dental Score (ADS; Janket et al, 2004). The ADS is a mathematically proper way to combine several oral health factors, and the likelihood ratios of these factors reflect their relative importance.…”
Section: (B) Case-control Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have further improved the TDI formulated by Mattila and co-workers in our case-control study by developing a mathematical scoring system called the Asymptotic Dental Score (ADS; Janket et al, 2004). The ADS is a mathematically proper way to combine several oral health factors, and the likelihood ratios of these factors reflect their relative importance.…”
Section: (B) Case-control Studiesmentioning
confidence: 99%
“…ADS has significantly facilitated the interpretation of several regression models, above and beyond CRP, HDL, and fibrinogen, all proven predictors of CVD. This suggests that oral health has the potential to affect systemic health via more than just the inflammatory process (Janket et al, 2004).…”
Section: (B) Case-control Studiesmentioning
confidence: 99%
“…Our group has reported that a mathematically summed score from several types of oral mucositis was significantly associated with coronary artery disease. 41 Some researchers postulated that the number of teeth might represent the effects of previous oral infection and additional diet-related proinflammatory process associated with cardiovascular pathogenesis. 42 However, the number of teeth appears to be a proxy for oral infection in cardiopathogenesis, because we found that our asymptotic dental score 41 was inversely correlated to the number of remaining teeth (γ = -0.8; P = .001).…”
Section: Combined Contribution Of Oral Health To Cvd Merging the 2 Pamentioning
confidence: 99%
“…Кроме того, при хроническом ПД установлено повышение частоты кардиоваскулярных и цереброваскулярных заболеваний независимо от традици-онных ФР [4, 8,29]. Выявление асимптомной ПП предложе-но использовать для скрининга ССЗ [30].…”
unclassified